Impacto de la aplicación del régimen simple de tributación frente a la informalidad en Colombia desde el año 2019 al 2022. (2023)
Informality is a problem found in all parts of the world, but it is more prevalent in developing countries, causing a rise in unemployment levels and a decrease in equity. For many years, the Colombian Government has been constantly looking for ways to reduce the high levels of informality that affect the country, and in the search, it has presented certain stumbling blocks that have prevented it from achieving favorable results, however, instead of giving in, it has decided to make improvements in its tax structure, creating a new mechanism for the reduction of the problem. This paper analyzes the data and characteristics of informality, such as its cause and effect; how the Simple Taxation Regime was constituted and the impact that the RST has had on the fight against informality since it came into force in 2019 until the end of 2022.